Attitude of bachelor of dental surgery students and interns toward teaching-learning process in Government Dental College, Kottayam, Kerala, India - Sandhya Gopalakrishnan; Philip Mathew; Kannan Vaidyanathan (Wolters Kluwer Medknow Publications, 2017)
Introduction: The educational environment affects the academic performance of students. One of the most widely utilized tools for measuring the educational environment is Dundee Ready Education Environment Measure (DREEM). The objective of the study was to assess the attitude toward study environment, as measured using DREEM questionnaire, and to find out the differences in perception of various batches of dental students. Materials and Methods: All Bachelor of Dental Surgery students from Government Dental College, Kottayam, Kerala, India, were included in the study. They were given the well-established DREEM questionnaire. A total of 234 students took part in the study, belonging to 2009, 2010, 2011, 2012, 2013, and 2014 batches. DREEM subcategories were analyzed for significance using analysis of variance. The significance of DREEM score across the different batches was further analyzed using post hoc test. Results: Overall, DREEM score was positive (111.14), but there is need for improvement. Individual questions also were given positive score for most questions. The maximum score was obtained for 3rd year students. Similar results are obtained for three of the five subcategories of DREEM. Conclusion: The total DREEM score was positive (111.14). The total score as well as the scores for the subcategories was highest in 3rd year dental students. The increase might be due to the excitement of clinical exposure for the first time in 3rd year students.